Iron‐Catalyzed Synthesis of Indenones through Cyclization of Carboxamides with Alkynes - Ilies, Laurean; Arslanoglu, Yasin; Matsubara, Tatsuaki; Nakamura, Eiichi (Wiley, 2018)
AbstractThe iron/diphosphine‐catalyzed annulation of a carboxamide possessing a bidentate directing group with an internal alkyne proceeds in the presence of phenylzinc halide as a base at 40 °C to produce a variety of indenone derivatives. The reaction proceeds through iron‐catalyzed C−H bond activation of the carboxamide, followed by insertion of the alkyne into the resulting iron intermediate, and cyclization accelerated by the presence of Lewis acidic ZnII. The reaction of naphthalene and anthraceneamide yields π‐conjugated indenone derivatives.